Bruxas: figuras de poder - (:unkn) unknown (Ministério Público do Estado da Bahia, 2005)
The women whom history and popular imagination mythicized as “witches” constitute figures that purge the phobias of the Counter Reformation. Witches were tortured and burnedto signal the dangers of practices and knowledge in the margins of the Church and other dominant institutions in the Modern Age. Midwives, healers and weepers, the witches blend intheir large kettle the mysteries of life and death inherited from pagan traditions. This papere xamines some historians’ texts, especially that of Jules Michelet, who created the witch’s romanticand martyred image, and the inquisitors’ manual Malleus Maleficarum, that describes the witch’spowers, her alliance with the demon and her threat to Christianity. These texts establish, through their different discourses, two opposing images: one that glorifies witches and another thatexecrates them, in order to show the transforming potential of their practices and their connection with sexuality.
Witches: Figures of power
Keywords: Bruxa; Sexualidade; Feitiçaria; Paganismo; Inquisição; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO